Genetics of type 2 diabetes mellitus and obesity--a review. - Jafar-Mohammadi, B; McCarthy, M (2008)
Type 2 diabetes (T2D) and obesity are recognized as conditions of growing biomedical importance to societies worldwide. Despite this, lack of understanding concerning the processes which normally serve to maintain weight and to regulate glucose concentrations, and ignorance about the mechanisms by which these homeostatic processes fail, remains a significant obstacle to the development of improved tools for management and prevention. There has been a long-standing belief that the identification of the specific genes influencing development of these conditions has the potential to reveal these fundamental processes, thereby providing vital clues to support clinical advances. Furthermore, there has been the hope that this information will translate into the capacity to deliver more 'personalized' medical care, whereby management can be tailored in accordance with an appreciation of individual molecular pathogenesis. As this review indicates, these developments are already a reality for selected monogenic forms of diabetes and obesity. Recent advances in the identification of genes underlying multifactorial forms of these conditions will accelerate efforts to effect similar clinical translation across the full spectrum of disease.